THE ANALYSIS OF SYNTAX ON LANGUAGE ACQUISITION OF THREE YEAR-OLD CHILDREN IN PERUM GRAHA MUKTI REGENCY KEDIRI - Nur Lailiyah; Linda Dwiyanti (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2018)
This study aimed at ascertaining: (1) the length of sentences obtained by three-year-olds, (2) sentence structure of three-year-olds, (3) average length of speech based on Mean Length of Utterance (MLU). This research applied descriptive qualitative method. The data collecting technique used interview, record, and note-taking techiques. Five children aged three years and a drift of a maximum of three months to be the object of this study. Conversations of children with parents and their families were recorded, then they were analyzed to find out the sentences they produce. The sentences produced by children were analyzed to find out  the sentence mode of sentence length, sentence structure, and average length of speech based on Mean Length of Utterance (MLU). The results showed that the acquisition of syntax in children aged three years within a maximum of three months in the Graha Mukti Regency showed the average has a MLU 2.327 is at stage V.